THE EFFECTIVENESS OF WORD JIGSAW STRATEGY ON STUDENTS’ VOCABULARY OF DESCRIPTIVE TEXT - Erniyanti Nur fatahhela Dewi (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
The article was aimed to find out the empirical evidence of the effectiveness of Word Jigsaw Strategy on Students’ Vocabulary achievement of Descriptive Text. Word jigsaw is part of graphic organizer which is one of alternative strategy to teach vocabulary. The study was quasi experimental research. The population was eight grade students of SMP PGRI 1 Ciputat. Moreover, the sample of this study consisted of 25 students from VIII-3 class in the Experimental Group and 25 students from VIII-4 in the controlled group. In this study, the experimental class was taught by using Word Jigsaw as strategy in teaching Vocabulary, while controlled class was taught without Word Jigsaw. The research instrument was test that consisted of pre-test and post-test form. The technique used in collecting data was quantitative with t-test. The result of this study showed that the use of Word Jigsaw strategy is effective on students’ vocabulary of descriptive text. It can be seen from the result of calculation that the students’ score in experimental class was higher than controlled class. Based on the statistical calculation with the significance level 5%, it showed that to = 2.778 was higher than tt = 2.021 as the effect size that ranged in moderate level. It meant the Word Jigsaw strategy was effective on students’ vocabulary achievement of Descriptive text.